The Relationship of Hemoglobin Drop with In-Hospital Mortality and Long-Term Morbidity and Mortality in Patients with Acute Coronary Syndrome - Polat, Fuat; Ohtaroğlu Tokdil, Nafia İnan Kardelen; Kılıçkıran Avcı, Burçak; Karadağ, Bilgehan; Öngen, Zeki (Cerrahpaşa Medical Journal, 2022)
Objective: The use of antithrombotic and anticoagulant drugs and invasive strategies increase the risk of bleeding in patients with acute coronary syndrome. It is not known to what extent the change in hemoglobin level determines the clinical outcome. Methods: Patients with the diagnosis of ST-elevation myocardial infarction, non-ST-elevation myocardial infarction, or unstable angina pectoris, who underwent coronary angiography, detected acute lesion, and followed in the coronary care unit were included in the study. The primary endpoint of the study was the composite outcome of in-hospital mortality, cardiac mortality, all-cause mortality, revascularization, and stroke. Results: The median follow-up period of a total of 208 patients was 23 ± 9 (1-34) months, mean age was 58.9 ± 12.6 years, 74.5% (n = 155) of the patients were male, and 74.5% (n = 155) were ST-elevation myocardial infarction. The mean difference between the hemoglobin before the procedure and the lowest hemoglobin until hospital discharge was 1.38 ± 1.37 mg/dL, and the highest difference was 7.3 mg/dL. No statistically significant correlation was found between the drop in hemoglobin and the composite endpoint. A drop of 3.25 mg/dL in hemoglobin affected the composite endpoint with a sensitivity of 11.42% and a specificity of 89.86% (likelihood ratio: 1.2). Conclusion: No significant relationship was found between the drop in hemoglobin and the composite outcome of in-hospital mortality, cardiac mortality, all-cause mortality, revascularization, and stroke. A low correlation was found between at least 3.25 mg/dL hemoglobin drop and composite outcome. Cite this article as: Polat F, İnan Kardelen Ohtaroğlu Tokdil N, Kılıçkıran Avcı B, Karadağ B, Öngen Z. The relationship of hemoglobin drop with in-hospital mortality and long-term morbidity and mortality in patients with acute coronary syndrome. Cerrahpaşa Med J. 2022;46(3):230-237.